THE RELATIONSHIP BETWEEN THE FUNDAMENTAL ENVIRONMENT RIGHT AND ECONOMIC DEVELOPMENT OF AGRIBUSINESS - Tamarindo, U. G. F.; Forti, J. C. (Revista Brasileira de Engenharia de Biossistemas, 2014)
The ecologically balanced environment, regardless of need every day of greater economic and social expansion, is human right, integrating the so-called third dimension of fundamental rights, and this protection, in turn; it is the duty of the State and, above all the collective. This right routinely ignored is ensured by the Constitution of the Federative Republic of Brazil, enacted on October 05 of 1988, and is directly related to the right to life of present and future generations. It is in Article 225 of the Brazilian Federal Constitution which is the broadest system and direct protection of the environment guardianships. It's musty that disrespect the environment is certainly one of the reasons why it appears today harmful climate change across the globe and especially the occurrence every day largest environmental disasters. In this context, serious environmental problems today and experienced the tragic consequences in climatic terms evidence alone, the urgent need to find new sustainable solutions and practice, to exhaustion, those already known also in relation to economic development activities linked to the agribusiness chain. The new and complex economic structure resulting from agribusiness is made today by numerous production networks, which do not always reveal sustainable forms of economic development with the preservation of the environment and ensuring social development. In that order, there is no denying that today these two objectives in many moments walk towards diametrically opposed. So for sustainable development to occur there needs to be harmonization concretely between economic development and the preservation of the environment, especially with regard to the extraction and use of natural resources.